Racing the Great White Way : Black Performance, Eugene O'Neill, and the Transformation of Broadway - Johnson, Katie N. (Book collections on Project MUSE., 2023)
The early drama of Eugene O'Neill, with its emphasis on racial themes and conflicts, opened up extraordinary opportunities for Black performers to challenge racist structures in modern theater and cinema. By adapting O'Neill's dramatic text-changing scripts to omit offensive epithets, inserting African American music and dance, or including citations of Black internationalism-theater artists of color have used O'Neill's dramatic texts to raze barriers in American and transatlantic theater. Challenging the widely accepted idea that Broadway was the white-hot creative engine of U.S. theater during the early 20th century, author Katie Johnson reveals a far more complex system of exchanges between the Broadway establishment and a vibrant Black theater scene in New York and beyond to chart a new history of American and transnational theater. In spite of their dichotomous (and at times problematic) representation of Blackness, O'Neill's plays such as The Emperor Jones and All God's Chillun Got Wings make ideal case studies because his work stimulated extraordinary, and underappreciated, traffic between Broadway and Harlem-between white and Black America. While it focuses on investigating Broadway productions of O'Neill, the book also attends to the vibrant transnational exchange in early to mid-20th century artistic production. Anchored in archival research, Racing the Great White Way recovers not only vital lost performance histories, but also the layered contexts for performing bodies across the Black Atlantic and the Circum-Atlantic.